2008
DOI: 10.1093/toxsci/kfn087
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-induced Activation of Stress Signaling Pathways, Disruption of Ubiquitin-dependent Protein Degradation and Apoptosis in Primary Rat Sertoli Cell-Gonocyte Cocultures

Abstract: Cadmium (Cd) is a ubiquitous environmental pollutant that has been associated with male reproductive toxicity in both humans and animal models. The underlying mechanism of this response, however, is still uncharacterized. To address this issue, we employed a recently developed and optimized three-dimensional primary Sertoli cell-gonocyte coculture system and examined the time- and dose-dependent effects of Cd on morphological alterations, cell viability, activation of stress signaling pathway proteins, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 60 publications
1
54
0
1
Order By: Relevance
“…19) Moreover, cadmium causes an increase in intracellular p53 protein levels and/or phosphorylated p53 protein levels in several cells. [57][58][59][60][61][62][63][64][65] These observations also support our findings that the p53-mediated pathway is one of the critical pathways for inducing apoptosis in chronic cadmium-exposed proximal tubular cells in the kidney.…”
Section: P53-dependent Pathwaysupporting
confidence: 87%
“…19) Moreover, cadmium causes an increase in intracellular p53 protein levels and/or phosphorylated p53 protein levels in several cells. [57][58][59][60][61][62][63][64][65] These observations also support our findings that the p53-mediated pathway is one of the critical pathways for inducing apoptosis in chronic cadmium-exposed proximal tubular cells in the kidney.…”
Section: P53-dependent Pathwaysupporting
confidence: 87%
“…Furthermore, other trace minerals may impact on genome stability. For instance, exposure to cadmium and lead has been reported to compromise the repair of oxidative DNA damage [Bolin et al, 2006, Yu et al, 2008. It will be important for future studies to reach a mechanistic understanding of how inorganic nutrients, either at nutritional or supranutritional levels, modulate DNA damage response and carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitinated proteins that are not degraded by the proteasome can accumulate and cause toxic cell damage. Previous studies have shown that Cd increases the accumulation of ubiquitinated proteins in several cell lines, such as mouse neuronal HT4 cells (Figueiredo-Pereira et al, 2002), rat sertoli cell-gonocyte cocultures (Yu et al, 2008) and rat proximal tubule cells (Thévenod and Friedmann, 1999). These findings suggest that Cd may cause toxic cell damage through the accumulation of unnecessary proteins.…”
mentioning
confidence: 80%